An evaluation of safe transportation of dangerous goods by road in Malaysia / Zuraidah Mohd Rais - Mohd Rais, Zuraidah (2016)
In Malaysia, as a result of her rapid expansion in the manufacturing sectors to accommodate the country's moving towards developed nation by year 2020, saw the increase in interstate shipments of dangerous goods by road in Malaysia. Although there has been no major accidents involving transportation of dangerous goods by road in Malaysia, the high rate of road accidents concerning motor vehicles has led to the increase concern on the risk of transporting the Dangerous Goods by road in Malaysia. This thesis aimed at investigating the factors that leads to safe transportation of Dangerous Goods in Malaysia and how far these factors has been practiced while transporting them. Survey as well as interview method had been used to investigate these factors on Dangerous Goods transporters and manufacturers in Malaysia. The thesis concluded that that factors affecting safe transport of dangerous goods by road in Malaysia includes I)Adequate and effective training provided to all personnel handling, storing and transporting Dangerous Goods 2)Correct and Adequate consignment procedures 3)Adequate enforcement and legal requirement being practice and 4)Correct setting of route for Dangerous Goods shipments.